Analisis Gagal Antar Paket Menggunakan Aplikasi Anylogic di SPP Bandung - Fadhilah, Faris Raid; Nurjuliyanto, Ilham; Wulandari, Raras Ayu (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
PT Pos Indonesia is an Indonesian State-Owned Enterprise (BUMN) engaged in postal services. PT Pos Indonesia has several types of services which will then be processed at SPP Bandung. PT. Pos Indonesia wants to always provide the best service for customers, but SPP Bandung still has problems in the process of its operational activities, namely failures between packets. The purpose of this study was to determine the factors that cause inter-package failures and corrective actions to minimize inter-package failures that occur. The research was conducted using the Anylogic application. The data used is the number of shipments and the number of failures between packets that occurred in October-December 2022. The Anylogic application uses Causal Loop Diagrams and Stock Flow Diagrams. Based on the analysis that has been carried out, information is obtained that the factors that cause failure between packets are empty houses, unknown addresses, empty house offices are still occupied (people/occupants of the house are away), and the recipient of the goods has changed address. Proposed actions/solutions taken to reduce the chance of failure between packets/return shipments at SPP Bandung include redelivering to the recipient’s address, contacting the recipient of the goods listed at the address listed, contacting the recipient of the goods to pick up the item at SPP Bandung, make returns, socialize at nearby addresses